Pengaruh Media Sosial dan Inovasi terhadap Kinerja Bisnis - Agus Dedi Subagja; Abu Muna Almaududi Ausat; Suherlan Suherlan (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2022)
Companies that want to survive in the era of information technology disruption characterized by hyperconnected business operations must quickly adopt social media technology. The problems faced by the business sector often delay the use of today's business models due to high anxiety. In fact, the role of digital marketing through the use of social media is very large. So, the company’s main key in responding to and seizing opportunities from this upheaval is innovation. The purpose of this study is to determine the effect of social media and innovation on SME business performance. The diffusion of innovations theory is used in this study as an affirmation that the implementation of technological innovation by SMEs is driven by the characteristics of innovation and organizational characteristics, bearing in mind that the current research unit of analysis is SMEs, namely organizations. In this research, to acquire a better understanding of the relationship between variables, quantitative approaches based on variance Structural Equation Modeling (SEM) and Partial Least Squares (PLS) were applied. Respondents were drawn from SMEs in the food and beverage sector in Surabaya, Indonesia, via an online questionnaire. The findings of this study provide positive and significant evidence between the role of social media utilization and innovativeness on SME performance. This means that SMEs in Surabaya have realized that social media is a very important tool for the success of a company. These technologies take information and knowledge sharing, interaction, and advertising to a higher level, resulting in benefits for organizations and customers. SMEs will fail and perish if they do not dare to innovate in technology.